2016
DOI: 10.1186/s12967-016-1010-x
|View full text |Cite
|
Sign up to set email alerts
|

Association of biomarkers with health-related quality of life and history of stressors in myalgic encephalomyelitis/chronic fatigue syndrome patients

Abstract: BackgroundMyalgic encephalomyelitis chronic fatigue syndrome (ME/CFS) is a common debilitating disorder associated with an intense fatigue, a reduced physical activity, and an impaired quality of life. There are no established biological markerof the syndrome. The etiology is unknown and its pathogenesis appears to be multifactorial. Various stressors, including intense physical activity, severe infection, and emotional stress are reported in the medical history of ME/CFS patients which raises the question whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 43 publications
2
30
0
Order By: Relevance
“…Many studies have found evidence of oxidative stress in CFS patients: increased levels of isoprostanes, peroxides and superoxide (that correlate with the severity of symptoms), reduced levels of antioxidants (including α-tochopherol), and impaired redox status as reflected in plasma levels of thiobarbituric acid reactive substances (which are correlated with the severity of symptoms) (10). Increased nitrosative stress has also been documented by increased levels of inducible nitric oxide synthase, nitric oxide, peroxynitrite, and nitrate.…”
Section: Studies Of Energy Metabolism Oxidative and Nitrosative Stressmentioning
confidence: 99%
“…Many studies have found evidence of oxidative stress in CFS patients: increased levels of isoprostanes, peroxides and superoxide (that correlate with the severity of symptoms), reduced levels of antioxidants (including α-tochopherol), and impaired redox status as reflected in plasma levels of thiobarbituric acid reactive substances (which are correlated with the severity of symptoms) (10). Increased nitrosative stress has also been documented by increased levels of inducible nitric oxide synthase, nitric oxide, peroxynitrite, and nitrate.…”
Section: Studies Of Energy Metabolism Oxidative and Nitrosative Stressmentioning
confidence: 99%
“…Bipolar Ag-AgCl surface electrodes (Medtronic, 13 L 20 Skovlunde, Denmark) were used to measure EMG voltage from the RF and FDL muscles on the dominant side of the body, as in previous studies [8][9][10][11][12][13]. The EMG signal was amplified (Nihon Kohden, Tokyo, Japan; common mode rejection ratio, 90 dB; input impedance, 100 mOhm; gain, 1000-5000) with a frequency band ranging from 10-10,000 Hz.…”
Section: Electromyography (Emg) Recording and Analysismentioning
confidence: 99%
“…All patients underwent an exercise session on a cycle ergometer up to their maximal work rate supported for a 1-min period, often limited by muscle fatigue. As in our previous studies [8][9][10][11]13], the protocol consisted of: (i) a 2-min rest period, during which all variables were measured and venous blood samples collected; (ii) a 1-min 20-W work load period used to reach the 1 Hz cycling frequency; (iii) a work period; and (iv) a 10-min recovery period. During the work period, the load was increased by 20 W every 60 s until fatigue obliged the subject to stop the exercise.…”
Section: Exercise Protocolmentioning
confidence: 99%
See 2 more Smart Citations